FACE IDENTIFICATION USING IMAGE PROCESING WITH THE NATIONAL INSTITUTE OF STANDARDS AND TECHNOLOGY (NIST) METHOD - Runtuwene, Eunike R.; Kumajas, Sondy; Kainde, Quido (Informatika, Universitas Jenderal Soedirman, 2024)
Cybercrime is a criminal act that utilizes technology, from devices to internet networks. The purpose of cybercrime cases is to harm others by committing theft, hacking, fraud, spreading viruses, and other digital crimes. In every cybercrime case there are usually traces of activity left behind, in the form of traces of activity (history) related can be used as evidence, both in the form of electronic evidence (in the form of electronic physical devices or storage media) and digital evidence (such as document files, history files, or log files containing relevant data). The National Institute of Standards and Technology (NIST) method is a method that is often used in digital forensics to overcome cybercrime cases. The National Institute of Standards and Technology (NIST) method is a method that aims for investigations in finding related information, in order to provide structured information, and process the information obtained. NIST refers to general principles such as collection, examination, analysis, reporting. Using the NIST (National Institute of Standards and Technology) method, the process at each stage is Data Collection is the process of collecting user data and face images through an easy-to-use user interface, Examination is the stage of processing images to detect faces using the Haar Cascade algorithm, Analysis is the process of training a face recognition model (LBPH) and applying it to recognize faces in images or videos. Reporting is the stage of displaying face recognition results and related information to the user through the GUI.